Feasibility of an integrated biomass-based CLC combustion and a renewable-energy-based methanol production systems. (December 2021) - Mancusi, E.; Bareschino, P.; Brachi, P.; Coppola, A.; Ruoppolo, G.; Urciuolo, M.; Pepe, F.
Abstract: An integrated process layout for methanol production comprising different systems is proposed and numerically investigated. The core of the layout consists of a multiple interconnected fluidized bed system for the chemical looping combustion (CLC) of solid fuels. A coupled hydrodynamic and reactive model of the CLC system was applied to evaluate solid circulation rate, solid bed levels in different parts of the system, flue gas composition and flow rate, and thermal power production. System performances were evaluated by considering chemical and physical properties of six types of Mediterranean area biomass as fuels and of CuO supported on zirconia as oxygen carrier, respectively. The methanol production unit was modelled as a network of four adiabatic fixed beds in series with interstage cooling and its performances were evaluated by considering that the CO/CO2 stream coming from the CLC unit reacts over Cu/ZnO supported on alumina catalyst with a pure H2 stream coming from an array of electrolytic cells. The number of cells was evaluated by considering that a constant hydrogen production for converting the whole carbon content of the gaseous stream produced by the CLC process must be attained. By considering that only energy coming from renewable sources was fed to the cells array, the capability of the proposed process to be used as an energy storage system for excess energy production from renewable sources was assessed. Highlights: Feasibility of a system coupling CLC and CO2 -to-methanol was numerically tested. Reduced CO2 emissions and a 30% electric energy storage efficiency was assessed. Performance benchmarking against a CO2 -to-methane system was numerically performed. Methanol synthesis is the best solution in terms of electric energy storage efficiency.